Antitumor Effect of Albendazole on Cutaneous Squamous Cell Carcinoma (SCC) Cells - Zhang, Qing-Ling (Biomed Res Int, 2019)
Drug repurposing and/or repositioning is an alternative method to develop new treatment for certain diseases. Albendazole was originally developed as an anthelmintic medication, and it has been used to treat a variety of parasitic infestations. In this study, we investigated the antitumor effect of albendazole and putative action mechanism. Results showed that albendazole dramatically decreased the cell viability of SCC cell lines (SCC12 and SCC13 cells). Albendazole increased apoptosis-related signals, including cleaved caspase-3 and PARP-1 in a dose-dependent fashion. The mechanistic study showed that albendazole induced endoplasmic reticulum (ER) stress, evidenced by increase of CHOP, ATF-4, caspase-4, and caspase-12. Pretreatment with ER stress inhibitor 4-PBA attenuated albendazole-induced apoptosis of SCC cells. In addition, albendazole decreased the colony-forming ability of SCC cells, together with inhibition of Wnt/β-catenin signaling. These results indicate that albendazole shows an antitumor effect via regulation of ER stress and cancer stemness, suggesting that albendazole could be repositioned for cutaneous SCC treatment.